Applied machine learning and high performance computing on AWS : accelerate development of machine learning applications following architectural best practices /: accelerate development of machine learning applications following architectural best practices. (2022) - Khanuja, Mani; Sabir, Farooq; Subramanian, Shreyas; Potgieter, Trenton
No abstract available